2022
DOI: 10.1186/s13063-022-06144-9
|View full text |Cite
|
Sign up to set email alerts
|

Success and failure factors of patient recruitment for industry-sponsored clinical trials and the role of the electronic health records—a qualitative interview study in the Nordic countries

Abstract: Background Patient recruitment for clinical trials is challenging—only approximately one third of all trials recruit their participants as planned. The pharmaceutical industry’s views on recruitment success have not been comprehensively investigated, although the industry globally conducts almost one third of all clinical drug trials. This study explored patient recruitment success and failure factors and the role of electronic health records (EHR) in the recruitment of trial participants in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…To accelerate conventional recruitment and reach recruitment targets, investigators often use static advertising tools such as flyers as well as electronic health records (EHR), including patient registries and databases [ 7 ]. In a recent study on industry-sponsored clinical trials, EHR were used in 85 % of surveyed Nordic trials, which is far above the 11 % reported globally [ 8 ]. Recruitment goals in Northern Europe, however, were only reached in half of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…To accelerate conventional recruitment and reach recruitment targets, investigators often use static advertising tools such as flyers as well as electronic health records (EHR), including patient registries and databases [ 7 ]. In a recent study on industry-sponsored clinical trials, EHR were used in 85 % of surveyed Nordic trials, which is far above the 11 % reported globally [ 8 ]. Recruitment goals in Northern Europe, however, were only reached in half of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that African Americans are less likely to both qualify for and to participate in clinical trials due to several reasons such as mistrust in the system, lack of interest in clinical trials, fear and stigma associated with participation, and a perception that they may not be compliant with trial protocols (107)(108)(109)(110). Several strategies that have improved clinical trial participation for minorities and the underserved in other diseases may also be deployed in sarcoidosis (108,111,112). These strategies center around the need to address mistrust and misconception, promote increased information and awareness of the benefits of trial participation, and ensure that investigators and study personnel are fully trained in cultural and racial competencies (108,112).…”
Section: Challenges Affecting Drug Trials and Drug Development In Sar...mentioning
confidence: 99%
“…As previously described, the enrollment of research participants can be subject to the influence of various factors. Many of these factors have been discerned through surveys, studies, and interviews involving participants, and, in case of minors, their parents, as well as investigators 16,17 . Nevertheless, certain limitations exist in some of these studies, including inadequately sample size justification, reliability, and validity of research instruments, and challenges in the collection of data 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Many of these factors have been discerned through surveys, studies, and interviews involving participants, and, in case of minors, their parents, as well as investigators. 16 , 17 Nevertheless, certain limitations exist in some of these studies, including inadequately sample size justification, reliability, and validity of research instruments, and challenges in the collection of data. 18 Furthermore, none of the aforementioned research endeavors has offered comprehensive list of facilitators and barriers to recruitment that effectively address this issue.…”
Section: Introductionmentioning
confidence: 99%